Validation of a measurement scale of service quality, image, customer satisfaction and loyalty in traditional trade - Cláudia Miranda Veloso; Ana Paula Monte (Tourism & Management Studies)
The retail industry’s ability to create satisfactory experiences for consumers remains to a considerable degree in the hands of management and retail staff. This research’s central purpose was to validate an instrument that assesses the perceived quality of service, brand image, customer satisfaction and loyalty to traditional retail stores in Portugal. The findings suggest that the scale’s 28 items can be grouped into four main dimensions and applied to Portuguese traditional retail businesses with good results. In addition, this questionnaire can be a useful tool for traditional retail stores seeking to understand customers’ perceptions. The assessment scale also facilitates the ongoing search for customer satisfaction and loyalty by revealing their drivers and moving traditional trade further along the path towards quality service and better brand image. These strategies, in turn, are reflected in excellent organisational performance and higher profitability.